Correlation Between Family Function with Stunting - Firdaus Wahyudi (Unnes Journal of Public Health, 2023)
Introduction: Stunting is a nutritional problem with a high prevalence in Indonesia. Stunting prevention and control efforts can be carried out with a family approach. The family, as the first and foremost environment for children, plays an important role in their growth and developmentAim: to analyze the correlation between family functions and stunting in toddlers. Method: An analytical observational study with a cross sectional design was conducted in July 2019 in the working area of the Kebondalem Health Center, Pemalang Regency with samples of children aged 6-24 months by cluster and consecutive sampling techniques. The variables were age, body length/height, immunization status, history of breastfeeding and complementary feeding. Also considered were history of infectious diseases, parental education level, family income, APGAR score (Internal Family Function), SCREEM score (External Family Function) and hygiene. Statistical analysis used a logistic regression test. Result: The number of samples were 142. The fixed model results were internal family function (APGAR) OR = 3.139 (p = 0.017; 95%CI 1.226-8,037), history of infectious disease OR = 2.875 (p = 0.008; 95%CI 1.325-6.236), mother's work status OR=0,353 (p=0,017; 95%CI 0,101 -1,232). Conclusion: There was a correlation between family function, history of disease and mother’s work status with stunting in toddlers.